Kinerja Produksi dan Daur Hidup Produk Agroindustri Aneka Bakery di Kota Cilegon - Meling Suneli; Wuryaningsih Dwi Sayekti; Adia Nugraha (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
This study aims to determine the production performance and product life cycle of Aneka Bakery. This research uses a case study method. Data collection was carried out in March 2020 with interviews, direct observation, and literature study. The analytical method used is quantitative descriptive analysis to analyze production performance and the product position based on the product life cycle. The results showed that the overall production performance was good. The productivity of baked and fried bread is 119 loaves / hour of work and 110 breads / hour of work with a capacity of> 0.5 and good quality of bread. The total profit of Aneka Bakery Agroindustry per day is Rp.631,067.85 with R / C> 1 (1.50 and 1.37) means that the bread business is profitable. The position of Aneka Bakery Agroindustry in the product life cycle is at the maturity stage.